Building a robust cyberthreat profile for institutions of higher educationd: an empirical analysis of external cyberattacks against a large University's computer network - Dollivera, Diana S. (International journal of law, crime and justice, 2021)
This study investigated twelve categories of exploits targeting a large southern university to build a build a more robust cyberthreat profile for institutions of higher education. In one week, the university experienced 12.4 million external cyberattacks from 110 countries. Malware constituted 58% of all malicious activities. Attacks were statistically more likely to occur during the overnight hours of weekdays. Moreover, the majority of cyberattack activity was generated by a limited number of IP addresses originating from a handful of countries. Dutch-originating IP addresses were responsible for 71% of all cyberattacks in this study, and spyware attacks almost exclusively originated from a single IP address in the U.S.